2020
DOI: 10.2987/20-6929.1
|View full text |Cite
|
Sign up to set email alerts
|

Deployment and Fact Analysis of the In2Care® Mosquito Trap, A Novel Tool for Controlling Invasive Aedes Species

Abstract: During April–October 2019, the West Valley Mosquito and Vector Control District (Ontario, CA) deployed large numbers of In2Care® mosquito traps in a preliminary study to evaluate the trap's potential effectiveness at controlling invasive Aedes aegypti (L.) and Ae. albopictus (Skuse) in 6 cities of San Bernardino County, CA. The trap was used to attract ovipositing females, expose them to the juvenile hormone mimic pyriproxyfen and the entomopathogenic fungus Beauveria bassiana, and autodisseminate pyriproxyfen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…The presence of the lid on the traps is preventing exposure of PPF to sunlight, which is probably causing the prolonged efficacy. These results are similar to the field study of Su et al [29] which showed a residual efficacy of the PPF in the traps after more than 29 weeks with a regular servicing every 3-4 weeks. Bukner et al [30] compared the efficacy of the In2Care traps and an integrated vector management (source reduction, larviciding and adulticiding) in a six months large field trial in Florida.…”
Section: Plos Onesupporting
confidence: 91%
“…The presence of the lid on the traps is preventing exposure of PPF to sunlight, which is probably causing the prolonged efficacy. These results are similar to the field study of Su et al [29] which showed a residual efficacy of the PPF in the traps after more than 29 weeks with a regular servicing every 3-4 weeks. Bukner et al [30] compared the efficacy of the In2Care traps and an integrated vector management (source reduction, larviciding and adulticiding) in a six months large field trial in Florida.…”
Section: Plos Onesupporting
confidence: 91%
“…Impacts on Culex mosquitoes, such as Cx. quinquefasciatus, which may use containers as larval habitats, were not quantified in this study, but like Su et al (2020), our field observations showed that In2Care traps may be attractive oviposition and resting sites for these mosquitoes as well. The possibility of having In2Care Traps available as a tool for reducing Cx.…”
Section: Discussionmentioning
confidence: 74%
“…We investigated: (1) habitat usage by invasive Aedes mosquitoes from 2016–2019, (2) suitability of the USDS habitat for invasive Aedes egg laying, hatching, and larval development, and (3) impact of Cx. quinquefasciatus larvae, the predominant mosquito species in urban southern California 16 , 17 , on Aedes oviposition preference and larval survival.…”
Section: Introductionmentioning
confidence: 99%